Patterns of ophthalmological complaints presenting to a dedicated ophthalmic Accident & Emergency department: inappropriate use and patients' perspective. Issue 11 (27th October 2008) - Hau, S; Ioannidis, A; Masaoutis, P; Verma, S
Abstract : Objectives: To investigate the appropriateness of patients attending an Accident & Emergency (A&E) department of an eye hospital, identify reasons for inappropriate use and propose recommendations in improving the provision of ophthalmic A&E care. Methods: A prospective questionnaire-based survey of consecutive patients who presented to the A&E department over a 7-day period was conducted. Patient demographic data, reason for attending from the patients' perspective, diagnosis, duration of symptom and management outcome were recorded. The diagnoses were grouped into acute and non-acute, and into those which were considered suitable to be seen in a primary care setting by specialist trained community general practitioners (GPs) or optometrists. Results: 560 completed questionnaires were evaluated; 171 cases (30.6%) were considered as non-acute and 210 (37.5%) were considered suitable to be seen by specialist trained community GPs or optometrists. 352 patients (62.8%) had symptoms for 1–6 days, 144 (25.7%) had symptoms for 1–4 weeks and 64 (11.5%) had symptoms for >1 month before presentation; in the latter two groups, 52 of the 208 patients (25%) were diagnosed with non-acute conditions. "Great concern" was the most common reason for attending the casualty department. 350 patients (62.5%) were discharged on the day of presentation. Conclusions: A significant number of patients who attend ophthalmic A&E departments have non-urgent conditions that could be managed satisfactorily in a primary care setting by specialist trained GPs or optometrists outside the hospital casualty department. Improvement in education of patients, the provision of specialist ophthalmic training for GPs and optometrists, and expansion of outpatient services are needed so that casualty remains a genuine emergency service.